Implementasi Metode Adaptive Power Law Transformation Dalam Perbaikan Citra Underwater - Nilmah Nilmah; Surya Darma Nasution; Siti Nurhabibah Hutagalung (JURIKOM (Jurnal Riset Komputer), 2020)
Although an image is rich in information, but often the image we have has a decrease in the quality (degradation) of the image that is a decrease in image quality, for example because it contains defects or noise (noise), the color is too contrast, less sharp, blurring, and so on. Of course this kind of image becomes more difficult to interpret because the information conveyed by the image is less clear. In the water environment, light factors greatly influence the results of the image quality obtained. With the deepening of underwater shooting, the results obtained will be the darker the quality of the underwater image. Underwater imagery is widely used as an object in various activities such as underwater habitat mapping, underwater environment monitoring, underwater object search. uneven lighting and bluish tones. One of the factors that influence the recognition results in pattern recognition is the quality of the image that is inputted. The image acquired from the source does not always have good qualit. To improve the quality of underwater images as stated above so that the information contained in the image can be well understood, a filtering method is needed, namely Adaptive Power Law Transformation. With this method and Microsoft Visual Basic 2008 program support is expected to produce a better image than before.